2002
DOI: 10.1523/jneurosci.22-03-00708.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Neuromuscular Junctions of the Slow and the Fast Excitatory Axon in the Closer of the CrabEriphia spinifronsAre Endowed with Different Ca2+Channel Types and Allow Neuron-Specific Modulation of Transmitter Release by Two Neuropeptides

Abstract: Most crustacean muscle fibers receive double excitatory innervation by functionally different motor neurons termed slow and fast. By using specific -toxins we show that the terminals of the slow closer excitor (SCE) and the fast closer excitor (FCE) at a crab muscle are endowed with different sets of presynaptic Ca 2ϩ channel types. -Agatoxin, a blocker of vertebrate P/Q-type channels, reduced the amplitude of EPSCs by decreasing the mean quantal content of transmitter release in both neurons by 70-85%, depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 67 publications
1
19
1
Order By: Relevance
“…Although it has been previously suggested that FMRFamidelike peptide-induced modulation of arthropod neuromuscular synapses can result from modulation of N-type calcium channels (Rathmayer et al, 2002), we provide strong evidence for an alternate modulatory pathway. An approximate third-or fourthpower relationship between transmitter release and calcium level at release sites suggests that changes in calcium influx are not responsible for the increased evoked calcium response (Jan and Jan, 1976;Robinson et al, 2002;Okamoto et al, 2005).…”
Section: Discussioncontrasting
confidence: 40%
“…Although it has been previously suggested that FMRFamidelike peptide-induced modulation of arthropod neuromuscular synapses can result from modulation of N-type calcium channels (Rathmayer et al, 2002), we provide strong evidence for an alternate modulatory pathway. An approximate third-or fourthpower relationship between transmitter release and calcium level at release sites suggests that changes in calcium influx are not responsible for the increased evoked calcium response (Jan and Jan, 1976;Robinson et al, 2002;Okamoto et al, 2005).…”
Section: Discussioncontrasting
confidence: 40%
“…Early studies in the locust suggested that FMRF-like peptides enhance synaptic transmission at the neuromuscular junction (Robb and Evans, 1994), and more recent studies in crustaceans suggest that these peptides modulate presynaptic Ca 2+ -channel activity (Rathmayer et al, 2002). In Drosophila, peptides produced from the FMRFa gene can also enhance synaptic efficacy at the neuromuscular junction when perfused…”
Section: Introductionmentioning
confidence: 99%
“…It was purified based on its myotropic actions on the insect hindgut, and was subsequently found to have wide distribution throughout the arthropods (2)(3)(4). In the crab Cancer, proctolin has potent effects on defined neural circuits within the stomatogastric system (5) and at the neuromuscular junction (6). In insects, proctolin is a major peptide cotransmitter and it modulates contractions of both somatic and visceral muscles (7,8).…”
mentioning
confidence: 99%